Enzymatic and proteomic exploration into the inhibitory activities of lemongrass and lemon essential oils against Botrytis cinerea (causative pathogen of gray mold) - Kgang, Itumeleng E.; Klein, Ashwil; Mohamed, Gadija G.; Mathabe, Patricia M. K.; Belay, Zinash A.; Caleb, Oluwafemi James (Frontiers in Microbiology, 2023)
Essential oils (EOs) have been demonstrated as efficacious against B. cinerea. However, the underpinning enzymatic and proteomic mechanism for these inhibitory effects is not entirely clear. Thus, this study examined the effects of lemon (Le) and lemongrass (Lg) EOs (individually and in combination) against B. cinerea based on enzymatic and proteomic analyses. Both EOs (individually and in combination) displayed abilities to induce scavenging as observed with the reduction of H2O2. Measured malondialdehyde (MDA) and superoxide dismutase (SOD) activity were increased in all EOs treated B. cinerea mycelia compared to the control. Ascorbate peroxidase (APX) activity was highest in Lg treated B. cinerea (206% increase), followed by combined (Le + Lg) treatment with 73% compared to the untreated control. Based on GC-MS analysis, the number of volatile compounds identified in lemon and lemongrass EOs were 7 and 10, respectively. Major chemical constituent of lemon EO was δ-limonene (71%), while lemongrass EO was α-citral (50.1%). Based on the interrogated LC-MS data, 42 distinct proteins were identified, and 13 of these proteins were unique with 1, 8, and 4 found in Le-, Lg-, and (Le + Lg) EOs treated B. cinerea, respectively, and none in control. Overall, 72% of identified proteins were localized within cellular anatomical entity, and 28% in protein-complexes. Proteins involved in translation initiation, antioxidant activity, protein macromolecule adaptor activity and microtubule motor activity were only identified in the Lg and (Le + Lg) EOs treated B. cinerea mycelia, which was consistent with their APX activities. Proteomics data are available via ProteomeXchange with identifier PXD038894